2 research projects looking at different methods of combatting antibiotic resistance - Fenn, S.J. (2017)
Both projects illustrate varying aspects that need to be explored to fully understand the problem of AMR and subsequently treat it. If we can determine the mechanism by which MDR emerges then we can begin implementing safeguards and start to identify high risk organisms or sequence type on the precipice of becoming a much larger problem. This enables to adopt a much more pre-emptive approach to combatting the problem of AMR as opposed to the reactive system we employ at present. This is essential considering the fact it take up to 15 years before new drugs combatting a new threat emerge and can be utilized effectively. If we can get ‘the jump’ on development of AMR and MDR we can cut down this timeframe. Microbial genomics will be essential in allowing us to almost track evolution in real time, determine new threats allowing mitigation of risk factors leading to development of drug resistance. Alternative therapies are needed to antibiotics to both reduce the chance of antibiotic resistance developing by lowering usage and to allow treatment of pan-resistant infections. These pan-resistant infections often occur in chronic P. aeruginosa infections in the CF lung leading to mortality. By targeting virulence factors of P. aeruginosa we hope to prove the concept of virulence inhibition and open research and the market to employing similar tactics with other pathogens. This is a small view of the range of skills needed to combat AMR. Every scientific discipline from microbiologists to biophysicists will be needed to combat this problem. The projects displayed employ computer science, bioinformatics, microbiology and eventually structural biology to answer questions about AMR and subsequently treat it. As our understanding of the problem grows, so does our chance of limiting the damage by AMR and enable up to continue to use these valuable resources.